ESBies: Safety in the tranches - Markus K. Brunnermeier; Sam Langfield; Marco Pagano; Ricardo Reis; Stijn Van Nieuwerburgh; Dimitri Vayanos (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
The euro crisis was fueled by the diabolic loop between sovereign risk and bank risk, coupled with cross-border flight-to-safety capital flows. European Safe Bonds (ESBies), a union-wide safe asset without joint liability, would help to resolve these problems. We make three contributions. First, numerical simulations show that ESBies would be at least as safe as German bunds and approximately double the supply of euro safe assets when protected by a 30%-thick junior tranche. Second, a model shows how, when and why the two features of ESBies - diversification and seniority - can weaken the diabolic loop and its diffusion across countries. Third, we propose a step-by-step guide on how to create ESBies, starting with limited issuance by public or private-sector entities.
Keywords: E44; G01; G28; 330; European Safe Bonds; safe assets; sovereign risk